To what extent can Hambrick and Fukutomi’s (1991) theory of seasons of CEO tenure explain today’s Youtuber phenomena? - Case study of Priya Patel (WonderWoman) - khan, i (2018)
This piece of research aims to explore whether the CEO seasons tenure model, devised by Hambrick and Fukutomi (1991) is applicable in explaining Youtuber performance over tenure. A single case study approach was used to analyse the performance of Priya Patel, a successful YouTube star who has been producing videos on YouTube for the last eight years under the brand name of WonderWoman. The case study found that the model was still applicable within the YouTube context, as an inverted U shape was seen in Youtuber performance. The findings from the case study reveal that the downturn in performance occurs at a faster rate due to industry dynamism, and the rapid increase in the following trends: information diversity, CEO power and task interest. Conclusively, the case study showcased that the complexity of the YouTube context, was what ultimately led to a quickened performance downturn.